2014
DOI: 10.1111/ijcp.12386
|View full text |Cite
|
Sign up to set email alerts
|

The impact of brief tobacco treatment training on practice behaviours, self-efficacy and attitudes among healthcare providers

Abstract: The value of a structured training experience was confirmed, and findings served to clarify the specific nature of training program impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
23
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 20 publications
(35 reference statements)
5
23
1
1
Order By: Relevance
“…This present study recorded significant improvements in knowledge, attitude and self-efficacy after the SCOPE training. It is in agreement with previous studies in which healthcare providers have reported improvements in knowledge, attitude and self-efficacy in smoking cessation intervention after training 3 10 33 42–48. This study suggests that the smoking status among SCOPE participants is essential, whereby there are no current smokers among the doctors, pharmacists and the nurses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This present study recorded significant improvements in knowledge, attitude and self-efficacy after the SCOPE training. It is in agreement with previous studies in which healthcare providers have reported improvements in knowledge, attitude and self-efficacy in smoking cessation intervention after training 3 10 33 42–48. This study suggests that the smoking status among SCOPE participants is essential, whereby there are no current smokers among the doctors, pharmacists and the nurses.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a higher degree of coordinated clinic system is needed to ‘Arrange’ follow-up cases for clinicians. There is a need for an integrated system-based approach involving multiple top-down stakeholders and environmental factors with the goal of connecting administrators, clinicians and staff to develop effective strategies to provide smokers with smoking cessation intervention 47. Apart from that, updated CPGs for treating tobacco use and dependence have emphasised the increasing evidence that the healthcare system significantly affects the likelihood that smokers receive effective smoking cessation intervention 9.…”
Section: Discussionmentioning
confidence: 99%
“…However, one must note that unlike our study, almost all participants (80.8%) had previous tobacco cessation training 26 . Training, which is known to have a positive impact on delivery of the 5As 29 - 31 , could have impacted on the above-mentioned results, eliminating differences by gender and years of experience. Although in our study professionals with more years of experience were more likely to see smoking cessation counselling as an inefficient use of their time, it could be that they had other nonclinical roles such as in management.…”
Section: Discussionmentioning
confidence: 99%
“…Given the opportunities provided by a significant reach into the smoking population, the clinical practice guidelines in many countries strongly recommend that health care practitioners briefly discuss evidence-based treatment options with all tobacco users at every visit (CAN-ADAPTT, 2011;Fiore et al, 2008;Health, 2007;NICE, 2013;). Practitioners, however, are generally unprepared to effectively discuss treatment options and are unfamiliar with the high intensity of treatment provided by TTSs (Applegate, Sheffer, Crews, Payne, & Smith, 2008;Payne et al, 2014;Sheffer, Anders, Brackman, Steinberg, & Barone, 2012;Steinberg, Alvarez, Delnevo, Kaufman, & Cantor, 2006).…”
mentioning
confidence: 99%